'Un'-blocking the industry 4.0 value chain with cyber-physical social thinking. Issue 2 (1st February 2023) - Mendhurwar, Subodh; Mishra, Rajhans
ABSTRACT: Integration of diverse technologies fuels business-model transformation, evolving new applications. Industry 4.0 utilizes emerging-technologies like IoT, AI to make next-generation manufacturing-processes more efficient and agile. Cyber physical systems (CPS) augmented with social, thinking technologies effectuate cyber physical social thinking systems (CPST). Distributed Ledger Technologies (DLT) like Blockchain are synergistic with architectural-elements of such industry-blueprints. Extant literature explores contextual-roles of distinct technology-components as-well-as their limited-combinations; clearly necessitating consideration of integrated-applications. This contemporary conceptual paper: (i) concisely analyses potential-synergies amongst Blockchain, CPST technologies; (ii) proposes novel integrated architecture; (iii) outlines underlying challenges, opportunities and performance considerations; bearing benefits beyond traditional-ecosystems to societal-stakeholders.